Mechanical properties and thermal behaviour of two-stage concrete containing palm oil fuel ash - Abdul Awal, A.S.M.; Wan Ibrahim, Mohd Haziman; Mohd Ali, Ahmad Zurisman; Hossain, M. Zakaria (Geotechnical, Construction Material & Environment, 2017)
Two-stage concrete (TSC) is a special type of concrete which is made by placing coarse aggregate in a formwork and injecting a grout either by pump or under the gravity force to fill the voids. Over the decades, the application of supplementary cementing materials in conventional concrete has become widespread, and this trend is expected to continue in TSC as well. Palm oil fuel ash (POFA) is one of the ashes which has been recognized as a good pozzolanic material. This paper presents the experimental results on the performance behaviour of POFA in developing physical and mechanical properties of two-stage concrete. Four concrete mixes namely, TSC with 100% OPC as a control, and TSC with 10, 20 and 30% POFA were cast, and the temperature growth due to heat of hydration and heat transfer in the mixes was recorded. It has been found that POFA significantly reduced the temperature rise in two-stage aggregate concrete and delayed the transfer of heat to the mass of concrete. The compressive and tensile strengths, however, increased with the replacement of up to 20% POFA. The results obtained and the observation made in this study suggest that the substitution of OPC by POFA is beneficial, particularly for prepacked mass concrete where thermal cracking due to extreme heat rise is of great importance.